Impact of hydrating status on residual renal function in hemodialysis patients (first report) - Surzhko, L.; Lubashev, V.; Poperechnyj, I. (Ukrainian Journal of Nephrology and Dialysis, 2019)
Residual kidney function (RKF) is a powerful indicator of residual renal functional capacity that eliminates uremic toxins and fluid in hemodialysis patients. The purpose of our study was to investigate the influence of hydrating status on residual renal function in patients with CKD 5HD. Methods. A prospective observational study included 60 hemodialysis patients with CKD VD. All patients were examined - taken general and biochemical blood tests, determined the level of urea and creatinine in the daily urine. RKF was evaluated by urine volume, residual KT / V and KRU. Water balance was measured and evaluated using BCM-monitor. Results.During the analysis of BCM data, hyperhydration (OH / ECW above 15%) was revealed in 15 among all patients included in the study, which amounted to 25%. A statistically significant difference between patients who were hyperhydrated and normohydrated was found in relative (OH / ECW) and absolute hydration (OH), ECW, and ultrafiltration rates. Thus, in the group of hyperhydrated patients, the average relative hydration rate was 14.3% lower compared to normohydrated patients (p < 0.001) and absolute hydration by 2.6 l (p < 0.001). In further analysis, no significant difference between two groups was found in the indicators characterizing the RKF, namely, between the level of urine output, KRU, KT / Vren. The level of ultrafiltration in the group with normal hydration is 900 ml lower than that with hyperhydration (p < 0.005). In study the influence of indicators of hydration status such as OH, OH / ECW, TBW, ECW, ICW on RKF indices no reliable correlation of the above mentioned values ​​with diuresis, KRU, KT / Vren (p > 0.05) was found. A positive correlation was found between KRU, diuresis and KT / Vren, indicating that with increasing diuresis the KRU value and KT / Vren increase (p < 0.001). The same relationship was found between diuresis and KT / Vren, p < 0.001. An analysis of the relationship between absolute and relative hydration with dialysis efficacy (eKT / V) revealed that dialysis efficacy decreases with increase of hydratation in CKD 5HD patients (p < 0.05). Conclusions. The results obtained in our study indicate that the indicators of hydration status at baseline do not allow to find out an influence of them on the baseline level of RKF (diuresis, KRU and KT / Vren) in patients with CKD 5HD. Issues of the influence of hydration status on changes in RKF during the observation will be addressed in the following reports.